Ein dunkelflügliges Weibchen von Calopteryx splendens bei Wesel/Niederrhein mit Diskussion der östlichen ssp. ancilla (Selys, 1853). - Schmidt, Eberhard G. (Contributions to Entomology = Beiträge zur Entomologie, 2006)
A dark-winged female of Calopteryx splendens was observed on 16.07.1995 on the Issel near Wesel through binoculars and recorded photographically (Fig. 1). It was a singleton amongst hundreds with the typical greenish-hyaline wings. Females with extensively dark wings are meant to be typical for the East European subspecies ancilla (Selys, 1853; "race de Prusse" from East Prussia according to Selys & Hagen, 1854), but recent data or photographic documentation of such specimens are hardly to be found in German language literature. In the majority of current identification works, dark-winged females, which at first glance resemble the male of C. virgo, are not included. The male of ancilla is characterized by the blue band on the wings reaching proximally much further than the nodus and distally mostly nearly or entirely to the wingtip (Fig. 2). A tendency towards this is to be observed in N. Germany (increasing from West to East) (Figs 3-4). Contrarily the dark colour of the wings in the few known females is of quite constant extent (as in Fig. 1). This speaks for a recessive-dominant "Yes-No" mechanism, which also explains the rarity in the transitional zone. There however remains a large deficit on the taxonomic and geographic delimitation of the subspecies. This contribution is to draw awareness to the dark-winged female form and to encourage monitoring of ancilla, particularly in the Oder / Neiße region and further east. Also included is a critical discussion of the terms "race" and of "andromorph / androchrome" for such colour forms, a remark on the value of molecular genetics for phylogenetic classification and the nomenclatural problems attached to ssp. ancilla in north-central Europe.KeywordsOdonata, subspecies, colour variety, distribution, sex dimorphism, Eastern Europe.